Potential expansion in the spatial distribution of subtropical and temperate west Australian sharks. Issue 4 (17th June 2021) - Bartes, Saia; Braccini, Matías
Abstract: Fishery‐dependent and ‐independent data collected since 1975 were examined to explore the spatial distribution of 30 shark and ray species in the west coast of Australia. Bigeye sixgill ( Hexanchus nakamurai ), tiger ( Galeocerdo cuvier ) and spinner ( Carcarhinus brevipinna ) sharks, and scalloped hammerhead ( Sphyrna lewini ) were observed >1000 and 300 km to the east of the edge of their reported distributions. Broadnose sevengill sharks ( Notorhyncus cepedianus ) and southern sawsharks ( Pristiophorus nudipinnis ) were observed >1000 km to the west of the edge of their reported distributions. Our study highlights the value of collecting and examining long time‐series of data for understanding the spatial distribution of large marine predators.